MASCoD—Multidimensional Assessment of Subjective Cognitive Decline - Maffoni, Marina; Pierobon, Antonia; Fundarò, Cira (Frontiers in Psychology, 2022)
Subjective cognitive decline (SCD) is a subclinical cognitive impairment that is complained by the individual without being objectively supported at clinical, diagnostic, and neuropsychological levels. It can negatively impact on patient’s frailty and quality of life, as well as on the caregiver’s burden. Moreover, it can be prodromal to Mild Cognitive Impairment or other types of dementia. Although the clinical manifestations of SCD can differ along with several cognitive domains, to date there are only screening tools to investigate subjective memory complaints. Thus, the first aim of this paper is to propose a preliminary English and Italian version of a new screening tool called MASCoD (Multidimensional Assessment of Subjective Cognitive Decline); the second aim is to propose its preliminary adoption on a pilot sample. This schedule is a brief test derived from the review of the literature and the clinical experience provided by an experts panelist. From pilot tests, it seems promising as it can help the professional to make differential diagnosis and to predict the risk of developing severe cognitive impairment over time, developing a personalised care path. This screening tool is brief, easily embeddable in usual clinical assessment, and administrable by different professionals. Furthermore, following validation, it will allow to collect manifold cognitive manifestations of SCD, addressing the shortage of previous validated instruments globally assessing cognition affected by this condition.